2012
DOI: 10.1007/s12594-012-0197-6
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Ruby Suite at Sardapur, Orissa: A Spectroscopic Investigation

Abstract: Orissa is an important area for gem variety of corundum deposits in India. Spectroscopic studies, such as ESR, OAS on samples from Sardapur, Orissa, were carried out to ascertain the colour cause of corundum. Electron spin resonance (ESR) spectroscopic study was carried out on the samples to detect the presence of paramagnetic ions i.e. Fe2+, Fe3+, Ti4+, Cr3+ and V3+ etc. The variable temperature experiment carried out to observe the effect of heating on peak valence state change in paramagnetic ions. Samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Of these bands at 401 nm (3.09 eV) and 535 nm (2.32 eV) are due to the spin allowed transition from the ground state 4 A 2g → 4 T 1g and 4 A 2g → 4 T 2g respectively. Such similar absorption bands due to both Cr and Fe have been reported for different ruby variety corundum samples by different authors (Cartier 2009;Majumdar and Mathew 2012). Figure 2a shows absorption spectra of the same sample before and after heat treatment.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Of these bands at 401 nm (3.09 eV) and 535 nm (2.32 eV) are due to the spin allowed transition from the ground state 4 A 2g → 4 T 1g and 4 A 2g → 4 T 2g respectively. Such similar absorption bands due to both Cr and Fe have been reported for different ruby variety corundum samples by different authors (Cartier 2009;Majumdar and Mathew 2012). Figure 2a shows absorption spectra of the same sample before and after heat treatment.…”
Section: Methodssupporting
confidence: 86%
“…This is the oldest mining region leading to findings of remains of Stone age and Bronze age. Ruby is also found in countries like Thailand, Vietnam, Sri Lanka, Russia, Greenland, Kenya, Tanzania, Pakistan, Afghanistan and some places in Odisha and Kashmir region in India (Atkinson and Kothavala, 1983;Majumdar and Mathew, 2012;Shor and Weldon, 2009). Corundum variety of gemstone show different colours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the absorption peak shifts to the purple area, the blue-purple tone of the ruby decreases, and the red hue increases, which is the main reason for the formation of the absorption band and the absorption peak moving to 385 nm and 388 nm, respectively. Such similar absorption bands due to both Cr and Fe have been reported for different rubies by previous research [20,25,37]. It has been observed that there is a decrease in the intensity of the band after heat treatment.…”
Section: Uv-visible Spectrasupporting
confidence: 89%
“…At Jhillingdara, Mishra and Mohanty [2] reported occurrences of ruby and corundum mineralization at the contact between metapyroxenite and granite gneiss and also eluvial placer ruby in the surrounding soil horizons. Mazumder and Mathiew [3] reported corundum (ruby) crystallization in the brecciated pegmatite at contact zones of granite gneiss of Bastar craton near Sardapur area.…”
Section: Introductionmentioning
confidence: 99%